Kolekcja Corneliusa Gurlitta – współczesne reminiscencje zjawiska grabieży żydowskich dzieł sztuki przez III Rzeszę Niemiecką - Pływaczewski, Wiesław (Studia Prawnoustrojowe, 2019)
The article presents the phenomenon of plundering works of art by German Nazis, as well as contemporary reminiscences of this practice. The author takes into consideration the media discovery in 2013, that refers to Gurlitt family collection. This occurrence has become an impulse to start a discussion about claims of the heirs of Holocaust victims against the museums and galleries that are in possession of works which provenance is doubly because of legal issues